Synergistically achieving ultrahigh energy-storage density and efficiency in linear-like lead-based multilayer ceramic capacitor. (1st April 2021) - Zhao, Ye; Meng, Xiangjun; Hao, Xihong
Graphical abstract: Image, graphical abstract Abstract: Although ceramic-based capacitors are indispensable component in advanced electrical systems, the recoverable energy-storage density ( W rec ) is often not satisfied. Herein, (Pb0.92 La0.02 Ca0.06 )(Zr0.6 Sn0.4 )0.995 O3 (PLCZS) multilayer ceramic capacitor (MLCC) is fabricated via a tape-casting technique and its energy-storage properties are analyzed in details. An ultrahigh W rec of 15.9 J cm −3 and a giant efficiency ( η ) of 92% are achieved synchronously at 760 kV cm −1 by virtue of its linear-like polarization-electric ( P - E ) hysteresis loop and ultrahigh breakdown strength (BDS). Meanwhile, PLCZS MLCC maintains high η (> 92%) within the frequency range of 1–100 Hz and the temperature range of 30–125 °C. In addition, a high discharge energy density ( W dis ) of 11.6 J cm −3 and a large power density ( P Dmax ) of 169.6 MW cm −3 are realized in PLCZS MLCC. These results demonstrate that PLCZS MLCC has a potential application in advanced power electrical systems.